O ensino religioso como facilitador do diálogo inter-religioso - Freitas, Janaína Santos Reus (2019)
This dissertation intends to approach the interreligious dialogue in the perspective of Faustino Teixeira, but always in communication with other authors and the Scripture. Specifically, it wants to demonstrate how the Curriculum Component of Religious Education can contribute to the interreligious dialogue being present in the school environment. In this sense, the following work responds to the following question: Religious Education is or is not a facilitator for interreligious dialogue? In the face of contemporaneity, where the presence of the various religions is a constancy, that with globality and technology we have access fast to the information and through them we know the cultural reality and within it the religious of diverse peoples, we come across groups that enter in conflicts before others. Thus, it is necessary to have a deep and practical reflection on the importance and relevance of the openness to the dialogue, considering the people no longer as opponents but as interlocutors who by means of a relational attitude see in otherness their support and condition for the construction of peace. After all, the divine rhyme has a peaceful attitude that through dialogue becomes learning and self-change from the other. Catholic theology has pointed to the confrontation of this new challenge of maintaining its identity no longer in the nullity of the others, on the contrary, in the experience of the dialogue with the other believing that the Holy Spirit is who directs everything and everything and that, therefore , is present in each of us.